Analisis Mekanisme Kegagalan Guide Vane dan Bottom Ring Akibat Erosi Sedimen pada Turbin Hidro - Moh. Ali Sidik; Komarudin Komarudin (P3M Politeknik Negeri Cilacap, 2026)
Sediment erosion is one of the primary causes of damage to the guide vane and bottom ring components of hydro turbines, resulting in reduced operational reliability and increased maintenance costs. Previous studies have mainly focused on coating materials, numerical simulations, or microstructural characterization separately, while the failure mechanism based on actual field damage has not been comprehensively explained. This study aims to investigate the failure mechanism of guide vane and bottom ring components subjected to sediment erosion using a forensic engineering approach. The investigation involved visual inspection, in-situ hardness testing, Micro Vickers hardness testing, and microstructural analysis using Scanning Electron Microscopy (SEM). The results revealed that the failure process initiated with the formation of microcracks in the protective coating, followed by coating adhesion degradation and coating spalling. Consequently, the exposed substrate experienced direct impacts from sediment particles, leading to crack propagation and progressive material loss. These findings provide a comprehensive understanding of the sediment erosion failure mechanism and can serve as a reference for improving inspection strategies, maintenance practices, and the durability of protective coatings in hydro turbines